FLAME MONITORING USING IMAGE CLASSIFICATION - Sawicki, Daniel (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
This paper presents comparison of image classification methods for co-firing biomass and pulverized coal. Two classes of combustion – stable and unstable were defined for nine variants with different power value parameters and fixed amount biomass. Experimental results show that correct classification of images was achieved for the assumed variants.